Nonlinearity compensation in laser diode by means feed-forward linearization for free space optical link - Idrus, Sevia Mahdaliza (Penerbit UTM, 2007)
Free-space optics, sometimes referred to as optical wireless, is the area in telecommunications research that has seen rapid development over the last several years, which is capable of offering high-bandwidth services over relatively short distances at attractive costs and obtains broadband communication. The dilemma in employing this technology is the performance reduction due to the nonlinearity present in the directly modulated optical transmitter, hence causes the inband, harmonic and intermodulation distortion (IMD) in the modulated signal. The technique of feedforward distortion compensation provides the better solution because it can minimize the (IMD3) in modulated optical signal operating at wavelength 1550nm, also reduces all the other higher orders of distortions. In this chapter a novel design for the free space optical link utilizing OFFLS (optical feed forward linearization system) which reduces non-linearity of the optical transmitter up to 17dB i.e. laser diode at carrier frequency 2.4GHz for the IEEE 802.11b/g standard and wavelength of 1550nm employing the feedforward linearization technique is presented.